User-centered design approaches to integrating intellectual property information into early design processes with a design patent retrieval application - Tang, Pinyan; Sun, Xu; Law, Effie Lai-Chong; Wang, Qingfeng; Cobb, Sue; Zhou, Xiaosong (Taylor and Francis Inc., 2019)
The relationship between intellectual property rights (IPRs) and the development of creativity is always a controversial topic. However, it has seldom been explored from the user-centered design (UCD) perspective. This paper describes how the UCD approach has been employed to develop Design Patent Retrieval Application (acronym: DsPLAi), a mobile app aimed to integrate IPRs related information into early design processes to enhance designers’ IP practice and to facilitate the creative process. Interview studies were first conducted to identify end-users’ understanding of IPRs and related practices. Next, participatory design workshops with designers and IP processionals were organized to understand the interaction between the two parties and their needs, thereby deriving requirements for DsPLAi. A prototype of the app was developed and evaluated with ten industrial designers. The prototype received positive feedback in the usability evaluation. The empirical results showed that the provision of IPRs related information at an early stage could be helpful to the design process and that the designers were positive about the use of DsPLAi in their daily design routines.